Australian Superannuation: The Current State of Play. (December 2016) - Chomik, Rafal; Piggott, John
Abstract: This article focuses on the challenges facing superannuation, the income replacement pillar of Australia's retirement income system, as it matures. We discuss four questions: In an era when households are making critical and complex choices that most have never previously confronted, how should policy‐makers and private providers guide choices? How should superannuation be taxed? How should the drawdown phase be structured? And to what extent will the Superannuation Guarantee be able to meet the objective of providing retirement income to substitute or supplement the age pension? This article attempts to provide perspective on each of the issues and concludes with a statement of research need.